Team-Based Care for Cancer Survivors With Comorbidities: A Systematic Review. Issue 5 (September 2022) - Doose, Michelle; Verhoeven, Dana; Sanchez, Janeth I.; Livinski, Alicia A.; Mollica, Michelle; Chollette, Veronica; Weaver, Sallie J.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Coordination of quality care for the growing population of cancer survivors with comorbidities remains poorly understood, especially among health disparity populations who are more likely to have comorbidities at the time of cancer diagnosis. This systematic review synthesized the literature from 2000 to 2022 on team-based care for cancer survivors with comorbidities and assessed team-based care conceptualization, teamwork processes, and outcomes. Six databases were searched for original articles on adults with cancer and comorbidity, which defined care team composition and comparison group, and assessed clinical or teamwork processes or outcomes. We identified 1, 821 articles of which 13 met the inclusion criteria. Most studies occurred during active cancer treatment and nine focused on depression management. Four studies focused on Hispanic or Black cancer survivors and one recruited rural residents. The conceptualization of team-based care varied across articles. Teamwork processes were not explicitly measured, but teamwork concepts such as communication and mental models were mentioned. Despite team-based care being a cornerstone of quality cancer care, studies that simultaneously assessed care delivery and outcomes for cancer and comorbidities were largely absent. Improving care coordination will be key to addressing disparities and promoting health equity for cancer survivors with comorbidities.